Detailed Multivariate Modeling of Beer Staling in Commercial Pale Lagers - Jaskula-Goiris, Barbara; De Causmaecker, Brecht; De Rouck, Gert; De Cooman, Luc; Aerts, Guido (BrewingScience, 2011)
It is generally recognized that flavour quality and flavour(in)stability cannot be grasped by one parameter, since the multitude of flavour chemicals involved. To identify beer chemistry changes during staling in commercial pilsner beer, an integrated analytical-sensorial methodology using multivariate statistical analysis was applied on samples subjected to ageing at 30 °C. Application of this technique to model the taste(in)stability in an objective way, offers the opportunity to more thoroughly investigate the influence of raw materials, brewing methods and applied technologies on flavour stability. The models obtained showed differences in aging behaviour of six commercial pale lager beers. Furthermore, detailed multivariate analysis allowed us to identify chemical compounds related to beer staling and facilitates a better understanding of beer flavour (in)stability by pinpointing the impact of process parameters and applied technologies.